2022
DOI: 10.1167/tvst.11.3.27
|View full text |Cite
|
Sign up to set email alerts
|

Intersession Repeatability of Structural Biomarkers in Early and Intermediate Age-Related Macular Degeneration: A MACUSTAR Study Report

Abstract: Purpose To analyze the intersession repeatability of structural biomarkers in eyes with early and intermediate age-related macular degeneration (iAMD) within the cross-sectional part of the observational multicenter MACUSTAR study. Methods Certified site personnel obtained multimodal imaging data at two visits (38 ± 20 [mean ± standard deviation] days apart), including spectral-domain optical coherence tomography (SD-OCT). One junior reader performed systematic and blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Images were graded by a junior reader followed by a senior reader and reviewed according to a standardized predefined grading protocol. 26 Inclusion and exclusion criteria have been previously published. 8,14 Briefly, in addition to satisfying disease classification criteria, participants were required to be aged between 55 and 85 years and able to provide informed consent and comply with study visits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were graded by a junior reader followed by a senior reader and reviewed according to a standardized predefined grading protocol. 26 Inclusion and exclusion criteria have been previously published. 8,14 Briefly, in addition to satisfying disease classification criteria, participants were required to be aged between 55 and 85 years and able to provide informed consent and comply with study visits.…”
Section: Methodsmentioning
confidence: 99%
“…Disease classifications were based on the Beckman classification system determined by a central reading center on the basis of multimodal imaging including color fundus photography, confocal infrared photography, fundus autofluorescence, and spectral-domain optical coherence tomography images obtained during a dedicated screening visit. Images were graded by a junior reader followed by a senior reader and reviewed according to a standardized predefined grading protocol . Inclusion and exclusion criteria have been previously published .…”
Section: Methodsmentioning
confidence: 99%
“…In the prospective European MACUSTAR study, participants with iAMD and neighboring disease stages (early AMD, late AMD) as well as healthy controls were clinically evaluated with multimodal imaging and functional testing for a study period of 3 years 8 , 36 . For the current analysis, images from the cross-sectional arm of the MACUSTAR clinical study with available QAF images (6 study sites, 120 participants) were included.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion and exclusion criteria of the MACUSTAR study have been reported elsewhere 7 . Briefly, subjects aged 55–85 at baseline, AMD (with the largest cohort being iAMD) or healthy eyes and the absence of other eye disorders were included 36 . iAMD was defined as bilateral large drusen and/or pigment abnormalities or extrafoveal geographic atrophy in the partner eye (for a full list of AMD disease stage criteria see Table 1 in Terheyden et al 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…The dense SD-OCT raster scan was primarily assessed for the determination of structural iAMD image features as follows, while other modalities provided complementary and confirmatory information 31 . Reticular pseudodrusen (RPD) were defined as hyperreflective irregularities and elevations above the RPE/Bruch's membrane band in SD-OCT imaging, presenting with medium-reflective mounds or cones at the level of the EZ or between the EZ and the RPE surface.…”
Section: Methodsmentioning
confidence: 99%